PENGEMBANGAN PRODUK BAKPAO SUBSTITUSI KACANG GUDE DIPERKAYA PROTEIN DAN SERAT PANGAN UNTUK LANSIA DI PANTI WREDA - Nasfati Iktarastiwi (Jurnal Pengabdian Masyarakat, 2025)
One of the unresolved nutritional problems in Indonesia is the problem of nutrition in the elderly. Many elderly people experience a lack of protein, vitamins, minerals and other nutrients. Pigeon pea is a plant that is still underutilized as a functional food that has nutritional content in the form of protein and dietary fiber. Pigeon pea also has the benefit of being able to cure chronic diseases and various degenerative diseases. This study aims to determine the nutritional content in the form of proximate levels and food fiber, then the public's acceptance of pigeon pea substitution buns (panelist preference test). This research is Research and Development with the Define, Design, Development, and Disseminate model. Research on community acceptance of 100 elderly panelists by filling in the preference test sheet provided. Descriptive analysis and paired sample t test (difference test) are the data analysis techniques used in this research. It is known that in the liking test, the level of liking for pigeon pea buns was obtained with an average value of 4.26. Pigeon pea buns have nutritional content per 100 grams consisting of 254 kcal of energy, 5 g of protein, 40 g of carbohydrates, 8 g of fat, and 10 g of dietary fiber. Pigeon pea buns can be a healthy alternative snack for elderly.